Theory and Evidence on the Liability of Relationship Commitment: Towards an Understanding of Why Vendor Firms Persist in Underperforming Customer Relationships - Bharadwaj, Sundar G. (Institutional Knowledge at Singapore Management University, 2005)
In this multi-method study, we extend and complement extant research on relationship commitment through rigorous field research and an in-depth cross-functional review to develop a model of the antecedents of vendor firmsÆ commitment to underperforming customer relationships. The conceptual model incorporates relationship-, performance-, organizational-, and investment-related factors as antecedents to vendor commitment. We then test the model with two survey-based studies, and compare and contrast the impact of these various antecedents across 382 underperforming and above-average performance customer relationships. The results indicate that continuity of relationship personnel, relationship age, performance stability, nature of performance change, visibility of the relationship, senior management involvement, orientation towards customer retention and risk, co-development, efficaciousness of the investment and resource commitment explain vendor firmsÆ commitment to under-performing relationships. In contrast, customer reputation, asset specificity along with relationship age, customer retention orientation and resource commitment are related to vendor firmsÆ commitment to above-average performance customer relationships. Further, using a conjoint type approach, we identify and rank-order (in terms of effectiveness) a set of remedial actions that vendor firms take to turnaround an underperforming customer relationship. Specifically, reframing the joint goals of the relationship, reevaluating internal processes, improving communications with the customer, developing better performance measurement systems, changing sales force compensation to be based on profitability and changing the relationship personnel are strategies for turning around underperforming customer relationships.